Tracking the migratory success of stocked European eels Anguilla anguilla in the Baltic Sea. Issue 2 (24th January 2013) - Prigge, E.; Marohn, L.; Hanel, R.
<x xml:space="preserve">Abstract</x> To investigate the extent to which European silver eels Anguilla anguilla, originating from stocking programmes in the Baltic Sea tributaries, effectively contribute to the spawning stock, two hundred and seventy‐four formerly stocked A. anguilla. emigrating from the Schwentine River near Kiel, Germany, were tagged with T‐Bar anchor tags. A total of 29 Anguilla spp. were recaptured (c. 11%) up to 14 months after release. Stocking history of recaptured A. anguilla. was confirmed by otolith microchemistry. Recapture locations were concentrated around the outlet of the Baltic Sea (Danish Belt Sea) with 62% of all recaptures reported here or in the Kattegat. Recaptured Anguilla spp. showed a reduction in both LT and mass (mean ± s.d. = −1·5 ± 0·9 cm and −125·3 ± 50·1 g) while average total fat content remained in the order of values previously reported as high enough to provide energy resources to allow successful completion of the spawning migration (mean ± s.d. = 28·4 ± 4·4%). The documented mean rate of travel (0·8 km day−1), however, indicated a delay in the target‐oriented migration that might be interpreted as a delayed initial migration phase of orientation towards the exit of the Baltic Sea.